2016
DOI: 10.18203/2320-1770.ijrcog20163193
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcome in gestational diabetes mellitus

Abstract: INTRODUCTIONPregnancy induces progressive changes in maternal carbohydrate metabolism. As the pregnancy advances insulin resistance and diabetogenic stress due to placental hormones necessitate compensatory increase in insulin secretion. When this compensation is inadequate, gestational diabetes mellitus (GDM) develops. Indian women have high prevalence of diabetes and their relative risk of developing GDM is 11.3 times compared to white women. 1A universal recommendation for the ideal approach for screening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
35
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 6 publications
15
35
3
Order By: Relevance
“…[18][19][20][21] Primi gravida was seen in 41,1% of the patients, while it was observed that on increase in the parity, the risk of GDM increases. Similar reports were observed by Dudhwadkar et al and Rajput et al 14,17 35.6% of the patients in our study had normal vaginal delivery, while 29.9% had elective surgery. Most if the patients who went in for caesarian section had babies with macrosomia.…”
Section: Discussionsupporting
confidence: 92%
“…[18][19][20][21] Primi gravida was seen in 41,1% of the patients, while it was observed that on increase in the parity, the risk of GDM increases. Similar reports were observed by Dudhwadkar et al and Rajput et al 14,17 35.6% of the patients in our study had normal vaginal delivery, while 29.9% had elective surgery. Most if the patients who went in for caesarian section had babies with macrosomia.…”
Section: Discussionsupporting
confidence: 92%
“…30 years. 21,22 In present study the occurrence of GDM among women ≥31 years was 18.6%. A study by Seshiah et al reported age more than 25 years is a risk factor for GDM.…”
Section: Resultssupporting
confidence: 46%
“…In present study, incidence of GDM in 25 -30 years old women was 70%, Amey Dudhwadkar et al study 5 it was 56% in 26 -30 years age. Incidence of GDM was 88% in women > 25 years age in Saima Yasmin Qadir et al study.…”
Section: Incidence Of Gdm In Different Studiessupporting
confidence: 45%
“…In present study GDM was detected in 64% multigravida, it was 72% in Amey Dudhwadkar et al study, 5 it was 76% in Saima Yasmin Qadir et al study, 6 while Randhawa et al 15 reported 80% GDM in multiparous women. So it indicates increasing parity is a risk factor for developing GDM.…”
Section: Incidence Of Gdm In Different Studiesmentioning
confidence: 45%
See 1 more Smart Citation